Approximation of Analytic Periodic Functions by de la Vallée-Poussin Sums - Rukasov, V. I.; Chaichenko, S. O. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate the approximation properties of the de la Vallée-Poussin sums on the classes \(C_{β }^q H_{ω }\) . We obtain asymptotic equalities that, in certain cases, guarantee the solvability of the Kolmogorov–Nikol'skii problem for the de la Vallée-Poussin sums on the classes \(C_{β }^q H_{ω }\) .